If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5=-3+6Y
We move all terms to the left:
-5-(-3+6Y)=0
We add all the numbers together, and all the variables
-(6Y-3)-5=0
We get rid of parentheses
-6Y+3-5=0
We add all the numbers together, and all the variables
-6Y-2=0
We move all terms containing Y to the left, all other terms to the right
-6Y=2
Y=2/-6
Y=-1/3
| -2(7a-6)+5a=84 | | X^2+4x40=180 | | 7.99×3x=72.83 | | -9n+7n=-2n | | -8(x-8)-2=126 | | 5-3A=7a-5 | | 13.21+0.11(x+3)=13.71-0.08 | | 3x+12=5x-32 | | -4(8a+4)+2=178 | | 3/4x+5=1/4x-7 | | -3(6a+4)-4=-106 | | -k-10=-6k+10 | | Y=X2+2x+4 | | 118.34=9.7v | | -8(-4-2n)-5n=87 | | 3/12x+2=-11 | | -7+9v=-4+9v | | -3(2y-7)+y=76 | | -3+4k=7 | | 10x-13x=86 | | 10x-13x=36 | | 6(-6k-1)+2k=-108 | | 66-4q/6q=3 | | 1,160x+2=6,690 | | 1/2x-4=1/3x+5 | | 8(4+7x)-3=309 | | 42-3v=4v | | -3p-5(-3p-5)=85 | | -9+2s=2s-9 | | 11-2.5x=x+7.5 | | 12m+24+12=12m+36 | | -2(-5+5n)+1=91 |